2012
DOI: 10.1371/journal.pone.0046553
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-10-Producing CD1dhighCD5+ Regulatory B Cells following Babesia microti-Infection

Abstract: BackgroundUnderstanding the induction of immune regulatory cells upon helminth infection is important for understanding the control of autoimmunity and allergic inflammation in helminth infection. Babesia microti, an intraerythrocytic protozoan of the genus Babesia, is a major cause of the emerging human disease babesiosis, an asymptomatic malaria-like disease. We examined the influence of acute B. microti infection on the development of regulatory B cells together with regulatory T cells.Principal FindingsOur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 22 publications
3
43
1
Order By: Relevance
“…Instead intra-erythrocyte parasite death was associated with elevated levels of the anti-inflammatory cytokines IL-10, and G-CSF. Other studies of B. microti infection, like the current study, noted serum IL-10 production but also reported modest elevation of serum pro-inflammatory cytokines including IFN-γ (33, 34), which we did not observe. IL-12p40 was also elevated; this cytokine can form homodimers that may play an antagonistic role in the development of IL-12p70 responses, though this remains unclear.…”
Section: Discussioncontrasting
confidence: 73%
“…Instead intra-erythrocyte parasite death was associated with elevated levels of the anti-inflammatory cytokines IL-10, and G-CSF. Other studies of B. microti infection, like the current study, noted serum IL-10 production but also reported modest elevation of serum pro-inflammatory cytokines including IFN-γ (33, 34), which we did not observe. IL-12p40 was also elevated; this cytokine can form homodimers that may play an antagonistic role in the development of IL-12p70 responses, though this remains unclear.…”
Section: Discussioncontrasting
confidence: 73%
“…Similar results suggesting the role of B cells in immune response regulation have been described in other murine models for autoimmune diseases, such as rheumatoid arthritis (RA) [9], autoimmune diabetes [10], and systemic lupus erythematosus (SLE) [11] as well as cancer [12] and other models of infectious diseases caused by bacteria, viruses, and parasites [13][14][15][16].…”
Section: B Cells As Immune Response Regulatorssupporting
confidence: 77%
“…The study by Ma, et al may be supported by this study. However, it should be noted that CD5, CD1d, or TIM-1 has not been established as surface markers in human regulatory B cells as opposed to mouse regulatory B cells 23,24…”
Section: Discussionmentioning
confidence: 99%